2018
DOI: 10.1016/j.diagmicrobio.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a two-stage testing algorithm for the diagnosis of respiratory viral infections

Abstract: New on-demand multiplex molecular respiratory viral diagnostics offer superior performance although can be expensive and some platforms cannot process multiple specimens simultaneously. We performed a retrospective study reviewing results of patients tested for respiratory viruses following introduction of a two-stage testing algorithm incorporating an initial screen with Sofia® immunoassay then secondary Biofire Filmarray®, and compared to a period when only Filmarray® was used. Of 2976 testing episodes, 1814… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Another study, using a decision-analysis approach in a pediatric patient population, concluded that testing using the Luminex xTag respiratory virus panel NAAT was less costly than other testing strategies when the prevalence of infection was ≥11%, with savings being primarily due to a reduction in the duration of hospitalization (58). Other groups have demonstrated potential laboratory cost savings associated with syndromic respiratory virus testing (59, 60) or a two-stage algorithm involving Quidel Sofia influenza antigen testing with reflex testing of negative samples with the BioFire FilmArray system (61). The contributions of the myriad coinfections diagnosed by syndromic testing to cost-effective respiratory virus testing remain an area of active investigation.…”
Section: Testing Methodsmentioning
confidence: 99%
“…Another study, using a decision-analysis approach in a pediatric patient population, concluded that testing using the Luminex xTag respiratory virus panel NAAT was less costly than other testing strategies when the prevalence of infection was ≥11%, with savings being primarily due to a reduction in the duration of hospitalization (58). Other groups have demonstrated potential laboratory cost savings associated with syndromic respiratory virus testing (59, 60) or a two-stage algorithm involving Quidel Sofia influenza antigen testing with reflex testing of negative samples with the BioFire FilmArray system (61). The contributions of the myriad coinfections diagnosed by syndromic testing to cost-effective respiratory virus testing remain an area of active investigation.…”
Section: Testing Methodsmentioning
confidence: 99%